IdentIRCCS. The description of healthcare professionals employed within IRCCS University Hospital of Bologna - Giusti, Martina; Quirini, Silvio; Peghetti, Angela; Durante, Stefano (Frontiers in Public Health, 2025)
Globally research centres in healthcare sector express the excellence in the translational medicine, from the evidence-based medicine to the evidence-based practice. In Italy, Institutes of Hospitalization and Healthcare with Scientific Goal (called IRCCS) are recognized as the driving force of innovation within healthcare sector. It is reasonable to expect that health professionals working within IRCCS institutions should embody professional excellence in a setting characterized by technological and organizational excellence. Nevertheless, in Italian public IRCCS, the personnel are selected by public competitions without any specific requirements in relation with the specific working context. According to the current state-of-art, this research aims to investigate the characteristic of healthcare professionals currently employed within Italian IRCCS facilities. IRCCS University Hospital of Bologna was chosen as suitable case study due to the enlargement of top management within the Healthcare Professions Directorate, that manifests a particular sensibility toward healthcare professionals growing. Dataset on personnel included sociodemographic information (age, sex, place of birth, residence, domicile), professional details (job category, role, working hours, training, allowances, contribution), and training status (household composition, number of children, number of dependents, physical limitations). The detailed description of healthcare professionals employed within the case study supports evidence-based decision-making for the development of corporate welfare policies and of targeted management strategies, useful and applicable in each healthcare research centre worldwide.